Epidemiological analysis of Elizabethkingia meningoseptica infection cluster among mechanically ventilated pediatric intensive care patients - Hamza, Wafaa Seddik; Morsi, Samar Saeed; Al Roomi, Ebtehal Saleh; Rotimi, Vincent Olubunmi (International Journal Of Community Medicine And Public Health, 2018)
Background: Elizabethkingia meningoseptica is frequently found in hospital environments and usually associated with healthcare-associated infections (HAIs), particularly in patients in the intensive care units (ICU). The current study report an outbreak of E. meningoseptica infection/colonization in the pediatric intensive care unit, highlighted the infection control methods used to stem the spread. Methods: During a period of 7 months, May-November 2015, 4 patients were infected/ colonized by E. meningoseptica. Infection control measures were re-emphasized after each case and environmental swabs were cultured to detect possible source. Follow up for 25 months to ensure eradication of the pathogen. Results: Four patients were colonized/ infected with E. meningoseptica, their mean age 22 months. The average time patients spent in ICU between admission and isolation of E. meningoseptica was 27.5±19.2 days. All patients were mechanically ventilated. 25% E. meningoseptica isolated from blood causing healthcare associated Central Line Associated Blood Stream Infection (CLABSI) while it was isolated from endotracheal tube (ETT) secretion in 75% as healthcare associated colonization. The 4 isolates confirmed as identical using pulsed field gel electrophoresis (PFGE). Conclusions: Intensive infection control measures including healthcare workers education, emphasizing hand hygiene, comprehensive cleaning and disinfection of equipment and the environment are important to eradicate the bacterium.